2012
DOI: 10.1016/j.jairtraman.2011.10.008
|View full text |Cite
|
Sign up to set email alerts
|

Airport logistics – A case study of the turn-around process

Abstract: This paper introduces the concept of airport logistics, along with a proof of concept through a case study where we model and optimize de-icing services at Stockholm Arlanda airport. The optimized schedule is tested using a simulation model of the turn-around process. The results demonstrate that a schedule taking into account the overall airport performance results in less delay than the schedule targeting solely the performance objective of the de-icing company.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
20
0
8

Year Published

2015
2015
2021
2021

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 34 publications
(28 citation statements)
references
References 3 publications
0
20
0
8
Order By: Relevance
“…Reference [12] reported that LCCs had accumulated around 34 per cent of the UK within 5 years from 1999-2004. According to [20], scheduling every operations in the turn-around enhances a better performance and efficiency, while [17] remark that sensor technology or checkpoints, would enhance a better turnaround within highly automated environment. Reference [21] concluded that the minimum time of turnaround operations are in domestic-domestic flight type when passenger stair are used for disembarking and air-bridge for boarding.…”
Section: Carrier's Market Sharementioning
confidence: 99%
“…Reference [12] reported that LCCs had accumulated around 34 per cent of the UK within 5 years from 1999-2004. According to [20], scheduling every operations in the turn-around enhances a better performance and efficiency, while [17] remark that sensor technology or checkpoints, would enhance a better turnaround within highly automated environment. Reference [21] concluded that the minimum time of turnaround operations are in domestic-domestic flight type when passenger stair are used for disembarking and air-bridge for boarding.…”
Section: Carrier's Market Sharementioning
confidence: 99%
“…After the air traffic control clearance, aircraft can use taxiway and go to the holding position. And then, aircraft takes off (Norin, 2008);  Arriving passenger: After the unloading of arriving passengers, they are carried to terminal building and wait for their baggage. Arriving passengers go out of the terminal, after they take baggage (Gatersleben & Weij, 1999); …”
Section: Introductionmentioning
confidence: 99%
“…To effi- 45 ciently coordinate the movement of passengers, crew, and aircraft, 46 either on the ground or in the air, is covered by many processes 47 where security is a key point for all areas involved. This raises 48 new challenges for several stakeholders, such as Air Traffic Control 49 (ATC) units, regulation agents, airlines, and Airport Management 50 companies, amongst others (Norin, 2008). 51 The major bottleneck created by this new scenario relates to 52 airspace congestion, a problem usually addressed through the 53 ground delay program (GDP), i.e., implementation of delays for air-54 craft still on the ground.…”
mentioning
confidence: 99%
“…The property that the slots are filled whenever possible 863 has been outlined in Hoffman (1997), the order of operations in 864 Vossen and Ball (2006), and unstable results as provided by the ori-865 ginal approach in Schummer and Rakesh (2013 processes (Norin, 2008). 872 The model that we propose solves the slot allocation problem 873 using Game Theory based on two-sided matching markets.…”
mentioning
confidence: 99%
See 1 more Smart Citation